Early Warning System for Rain-Induced Mass Movement for Ciudad Bolívar (Colombia) - Gutiérrez Alvis, David Esneider; Bornachera Zarate, Leydy Stefany; Mosquera Palacios, Darin Jairo (Ingeniería Solidaria, 2018)
Introduction: This research article introduces an early warning system for rain-induced mass movement for the district of Ciudad Bolívar, in Bogotá, Colombia, developed at the Universidad Distrital Francisco José de Caldas in 2018. Methods: A sensor network was developed by means of a base station, which is responsible for issuing a warning if there is a risk of landslide. Results: The data provided by the sensor network, such as humidity and temperature, issue warnings to increase the possibility of saving the lives of vulnerable population in the district. Conclusion: This project seeks to save the most important thing a human being has: his life. In addition to raising awareness among individuals of the danger of building houses in places with a high risk of landslides, the aim is to show that through technology we could save lives, warning about natural disasters such as landslides. Originality: In this work, a previous soil survey was conducted in Ciudad Bolívar and a warning scale was created for the system, implementing the Risk Management and Climate Change Information System ( sire ) in the district. Limitations: Scarce development of rain-induced landslide warning systems in Colombia.